2024
DOI: 10.26599/fshw.2022.9250089
|View full text |Cite
|
Sign up to set email alerts
|

A core-satellite self-assembled SERS aptasensor containing a “biological-silent region” Raman tag for the accurate and ultrasensitive detection of histamine

Abstract: Herein, a novel interference-free surface-enhanced Raman spectroscopy (SERS) strategy based on magnetic nanoparticles (MNPs) and aptamer-driven assemblies was proposed for the ultrasensitive detection of histamine. A core-satellite SERS aptasensor was constructed by combining aptamer-decorated Fe 3 O 4 @Au MNPs (as the recognize probe for histamine) and complementary DNA-modified silver nanoparticles carrying 4-mercaptobenzonitrile (4-MBN) (Ag@4-MBN@Ag-c-DNA) as the SERS signal probe for the indirect detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The result demonstrated that the Ag layer coating greatly enhanced the SERS signal of the 4-MBN on the surface of the Au NSs, which was expected due to the coupled electromagnetic "hot spots" generated within the noble metal nanogap structure (i.e., hot spots formed between the Au NSs and Ag coating layer). 10,50 To further demonstrate that the SERS signal enhancement was not simply due to an increase in nanoparticle size (since larger nanoparticles show stronger Raman scattering enhancing effects), 4-MBN was adsorbed on the surface of the Au NSs@ Ag nanostructure. The intensity of the 4-MBN peak in the "biological silent" region was only ∼34.1% of the intensity of Au NSs@4-MBN@Ag (Figure S11, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The result demonstrated that the Ag layer coating greatly enhanced the SERS signal of the 4-MBN on the surface of the Au NSs, which was expected due to the coupled electromagnetic "hot spots" generated within the noble metal nanogap structure (i.e., hot spots formed between the Au NSs and Ag coating layer). 10,50 To further demonstrate that the SERS signal enhancement was not simply due to an increase in nanoparticle size (since larger nanoparticles show stronger Raman scattering enhancing effects), 4-MBN was adsorbed on the surface of the Au NSs@ Ag nanostructure. The intensity of the 4-MBN peak in the "biological silent" region was only ∼34.1% of the intensity of Au NSs@4-MBN@Ag (Figure S11, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For instance, Chen et al proposed an interference-free SERS strategy based on magnetic-driven component, in which 4-mercaptobenzonitrile (4-MBN) operating in the "biological-silent" region was embedded into Ag NPs as SERS tag. 10 Liu et al showed that the Prussian blue had a strong and sharp band in the "biological-silent" region. 44 Li et al achieved 32 resolvable colors in the "biological-silent" region by studying various biological orthogonal Raman molecules containing C�N and C�C with different electronic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An indirect SERS-tag strategy, specific for His detection, is described by Chen C. et al [86]. The substrate is made up of magnetic Fe 3 O 4 @Au-aptamer nanoparticles that represent the histamine recognize probe and of a complementary DNA (c-DNA) carrying an Ag@4-MBN@Ag system which is the SERS signal probe.…”
Section: Sers Detection Of Sudan In Saffron and Other Spicesmentioning
confidence: 99%